Frequency of vacA, cagA and babA2 virulence markers in Helicobacter pylori strains isolated from Mexican patients with chronic gastritis - Negrete Erasmo; Camacho Ausencio; Cortés José; Rodríguez Cristina; Arroniz Salvador; Rodríguez Raymundo; Monroy Eric; Paniagua Gloria; Vaca Sergio (BMC, 2009)
Abstract Background Helicobacter pylori has been strongly associated with chronic gastritis, peptic and duodenal ulcers, and it is a risk factor for gastric cancer. Three major virulence factors of H. pylori have been described: the vacuolating toxin (VacA), the cytotoxin-associated gene product (CagA) and the adhesion protein BabA2. Since considerable geographic diversity in the prevalence of H. pylori virulence factors has been reported, the aim of this work was to establish the H. pylori and vacA, cagA and babA2 gene status in 238 adult patients, from a marginal urban area of Mexico, with chronic gastritis. Methods H. pylori was identified in cultures of gastric biopsies by nested PCR. vacA and cagA genes were detected by multiplex PCR, whereas babA2 gene was identified by conventional PCR. Results H. pylori-positive biopsies were 143 (60.1%). All H. pylori strains were vacA+; 39.2% were cagA+; 13.3% were cagA+ babA2+ and 8.4% were babA2+. Mexican strains examined possessed the vacA s1, m1 (43.4%), s1, m2 (24.5%), s2, m1 (20.3%) and s2, m2 (11.9%) genotypes. Conclusion These results show that the Mexican patients suffering chronic gastritis we have studied had a high incidence of infection by H. pylori. Forty four percent (63/143) of the H. pylori strains analyzed in this work may be considered as highly virulent since they possessed two or three of the virulence markers analyzed: vacA s1 cagA babA2 (9.8%, 14/143), vacA s1 babA2 (4.9%, 7/143), and vacA s1 cagA (29.4%, 42/143). However, a statistically significant correlation was not observed between vacAs1, cagA and babA2 virulence markers (χ2 test; P > 0.05).